USE OF COMPOUNDS NATURAL IN REDUCING THE BACTERIAL LOAD OF THE ORAL CAVITY: A REVIEW ARTICLE - Santos-Zambrano, Thaináh Bruna (2020)
Currently, there is a wide range of pharmaceutical products that off er great benefi ts for the treatment of various oral diseases. Most of these products are of synthetic origin with antibacterial properties but there are the numerous side eff ects associated with their use. An alternative is the use of natural products from plants and insects in the reduction of the bacterial load of the oral cavity as chamomile (Chamaemelum nobile (L.) All.), cocoa (Th eobroma cacao L.), aloe (Aloe vera L.), moringa (Moringa oleifera Lam.), oregano (Origanum vulgare L.), coconut (Cocos nucifera L.), garlic (Allium sativum L.), clove (Syzgium aromaticum L.), cardamom (Elettaria cardamomum L.), stevia (Stevia rebaudiana Bertoni), honey bee and propolis, addressed in this literature review. Th is review attempts to address the use of diff erent natural compounds in reducing the bacterial load of the oral cavity. It can be concluded that there are several studies about the eff ects of natural products on the part of man in medicine, where there are a large number of works and publications related to natural substances with active ingredients in reducing the bacterial load of the oral cavity.